2017
DOI: 10.15835/nbha45110569
|View full text |Cite
|
Sign up to set email alerts
|

Short-Time of Rehydration is not Effective to Re-Establish Chlorophyll Fluorescence and Gas Exchange in Two Cowpea Cultivars Submitted to Water Deficit

Abstract: Low water supply frequently interferes on chlorophyll fluorescence and gas exchange. This study aimed to answer if a short-time of rehydration is efficient to re-establish chlorophyll fluorescence and gas exchange in cowpea plants. The experiment used four treatments (sensitive / water deficit, sensitive / control, tolerant / water deficit and tolerant / control). The sensitive and tolerant cultivars after water restriction had significant changes in gas exchange. On the third day, the stress caused lower for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Steroid application attenuated the effect of water deficit on WUE, and this response was related to the combined increases in P N and E , verified in this study, because WUE is the physiological variable that expresses the amount of carbon fixed ( P N ) per plant per unit of lost water ( E ) (Barros Junior et al, 2017). The increase in P N / C i in plants treated with EBR indicated that the steroid increased the assimilation of CO 2 ( P N ) with concomitant reduction of the concentrations of C i due to the increase in the activity of the enzyme RuBisCO (Lima & Lobato, 2017; Yusuf et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…Steroid application attenuated the effect of water deficit on WUE, and this response was related to the combined increases in P N and E , verified in this study, because WUE is the physiological variable that expresses the amount of carbon fixed ( P N ) per plant per unit of lost water ( E ) (Barros Junior et al, 2017). The increase in P N / C i in plants treated with EBR indicated that the steroid increased the assimilation of CO 2 ( P N ) with concomitant reduction of the concentrations of C i due to the increase in the activity of the enzyme RuBisCO (Lima & Lobato, 2017; Yusuf et al, 2011).…”
Section: Discussionsupporting
confidence: 74%